Design, Synthesis of Some Novel Thiazolidin-4-one Derivatives Bearing Benzimidazole Nucleus and Biological Evaluation of their Possible in vitro Antiinflammatory as Cyclooxygenase Inhibitors and Antioxidant Activity - Sahoo, U.; Seth, A.K.; Balaraman, R.; Velmurugan, R. (Asian Journal of Chemistry, 2015)
A series of 2-[2-(4-cyanophenyl)-6-substituted-1H-benzimidazol-1-yl]-N-[2-(substituted)-4-oxo-1,3- thiazolidin-3-yl]acetamide [9(I-XXXI)] were synthesized. Substituted o-phenylenediamine was reacted with substituted 4-cyanobenzaldehydes in the presence of sodium metabisulfite to furnish substituted 2-(4-cyanophenyl)-1H-benzimidazoles (1). When these substituted 2-(4-cyanophenyl)-1H-benzimidazoles were further treated with ethyl chloroacetate in KOH/DMSO, N-alkylated product (2-(4-cyanophenyl)-benzimidazol-1-yl)-acetic acid ethyl esters (2) was formed. To synthesize 2-(4-cyanophenyl)-benzimidazol-1-yl-acetic acid hydrazides (3) chemical reactions were conducted between hydrazine hydrate and the esters (2). When a mixture of 2-(4-cyanophenyl)-benzimidazol-1-yl)-acetic acid hydrazide (3) react with substituted aldehydes in ethanol was reflux, imines intermediates [4(I-XXXI)] was formed. To synthesize 9(I-XXXI) reactions were occurred between a mixture of imine intermediate and thioglycollic acid in dioxane. The structures of newly synthesized compounds 9(I-XXXI) was confirmed by spectroscopic techniques. All the synthesized compounds were screened for its in vitro antioxidant and antiinflammatory activity. The in vitro antioxidant and antiinflammatory activity might be attributed due to the presence of more electrons withdrawing group and moiety having more lipophilicity also more electronegativity in nature.